Propolis attenuates oxidative injury in brain and lung of nitric oxide synthase inhibited rats - Zeliha Selamoglu-Talas; Ilknur Ozdemir; Osman Ciftci; Oguz Cakir (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: The blocking of nitric oxide synthase (NOS) activity may reason vasoconstriction with formation of reactive oxygen species. Propolis has biological and pharmacological properties, such as antioxidant. The aim of this study was to examine the antioxidant effects of propolis which natural product on biochemical parameters in brain and lung tissues of acute nitric oxide synthase inhibited rats by Nω-nitro-L-arginine methyl ester (L-NAME). Methods: Rats have been received L-NAME (40 mg/kg, intraperitoneally), NOS inhibitor for 15 days to produce hypertension and propolis (200mg/kg, by gavage) the lastest 5 of 15 days. Results: There  were  the  increase  (P<0.001)  in  the  malondialdehyde  levels  in  the  L-NAME treatment groups when compared to control rats, but the decrease (P<0.001) in the catalase activities in both brain and lung tissues. There were statistically changes (P<0.001) in these parameters of L-NAME+propolis treated rats as compared with L-NAME-treated group. Conclusion: The application of L-NAME to the Wistar rats resulted in well developed oxidative stress. Also, propolis may influence endothelial NO production. Identification of such compounds and characterisation of their cellular actions may increase our knowledge of the regulation of endothelial NO production and could provide valuable clues for the prevention or treatment of hypertensive diseases and oxidative stress.